Plant NLRs get by with a little help from their friends. (August 2020) - Feehan, Joanna M; Castel, Baptiste; Bentham, Adam R; Jones, Jonathan DG
Abstract : Many plant NLR (nucleotide-binding, leucine-rich repeat) immune receptors require other NLRs for their function. In pairs of chromosomally adjacent sensor/helper NLRs, the sensor typically carries an integrated domain (ID) that mimics the authentic target of a pathogen effector. The RPW8-NLR clade supports the function of many diverse plant NLRs, particularly those with a TIR N-terminal domain, in concert with a family of EP-domain containing signalling partners. The NRC clade of NLRs are required for the function of many unlinked sensor NLRs in Solanaceous plants. We evaluate recent advances in paired NLR biology in the context of the structure and possible mechanisms of the first defined plant inflammasome containing ZAR1.